"It's paradise there, I saw it on TV": Psychological wellbeing, migratory motivators, and expectations of return among West African migrants. Issue 1 (2nd January 2020) - Veronese, Guido; Pepe, Alessandro; Addimando, Loredana; Sala, Giovanni; Vigliaroni, Marzia
Abstract: The main objective of the present quali-quantitative exploratory study was to analyze narrative data from in-depth interviews with returning West African migrants in the Agadez and Nyamey regions (Niger). Specifically, we out to investigate the complex set of reasons that had led the participants to leave their homes and move toward other countries, as well as their expectations concerning their return to their home country and the implications of return for their subjective wellbeing. Categorical analysis of the interview transcripts led us to identify two main first-order themes (internal and external factors underpinning the decision to migrate) and seven lower-order classes of reasons for migrating. We drew on a pragmatically informed Quantitative Textual Analysis approach to further explore the data, finding that experience strongly influenced migrants' representations and aspirations, as well as their expectations surrounding their return migration. The more migrants encounter hardship and deprivation in the destination country, the more their subjective wellbeing can be undermined, and consequently, the more their expectations about return are catastrophic. Familial and personal aspirations surrounding the migratory project appear to increase these migrants' sense of failure and despair on returning home without the economic and personal resources to support themselves and their families. We discuss the implications for practitioners and policy makers.